Follow-up of young adult monozygotic twins after simultaneous critical coronavirus disease 2019: a case report - de Castro, Mateus V.; Silva, Monize V. R.; Soares, Flávia B.; Cória, Vivian R.; Naslavsky, Michel S.; Scliar, Marilia O.; Castelli, Erick C.; de Oliveira, Jamile R.; de Medeiros, Giuliana X.; Sasahara, Greyce L.; Santos, Keity S.; Cunha-Neto, Edecio; et al. (Frontiers in Medicine, 2022)
Background: The influence of the host genome on Covid-19 susceptibility and severity is supported by reports on monozygotic (MZ) twins where both were infected simultaneously with similar disease outcomes, including several who died due to the SARS-CoV-2 infection within days apart. However, successive exposures to pathogens throughout life along with other environmental factors make the immune response unique for each individual, even among MZ twins. Case presentation and methods: Here we report a case of a young adult monozygotic twin pair, who caught attention since both presented simultaneously severe Covid-19 with the need for oxygen support despite age and good health conditions. One of the twins, who spent more time hospitalized, reported symptoms of long-Covid even seven months after infection. Immune cell profile and specific responses to SARS-COV-2 were evaluated as well as whole exome sequencing. Conclusions: Although the MZ twin brothers shared the same genetic mutations which may be associated with their increased risk of developing severe Covid-19, their clinical progression was different, reinforcing the role of both immune response and genetics in the Covid-19 presentation and course. Besides, the post-covid syndrome was observed in one of them, corroborating an association between the duration of hospitalization and the occurrence of long-covid symptoms.